Kinds behaving badly: intentional action and interactive kinds. - Allen, Sophie R. (Synthese)
This paper investigates interactive kinds, a class of kinds suggested by Ian Hacking for which classification generates a feedback loop between the classifiers and what is classified, and argues that human interactive kinds should be distinguished from non-human ones. First, I challenge the claim that there is nothing ontologically special about interactive kinds in virtue of their members being classified as such. To do so, I reject Cooper's counterexample to Hacking's thesis that kind descriptions are necessary for intentional action, arguing that classification (although not necessarily linguistic description) is required for intentional action. Having considered ways to characterise the metaphysics of interactive kinds and the semantics of kind terms, I argue that the fact that classification facilitates intentional action makes human interactive kinds ontologically distinctive because of the anomalous nature of the change which the kind-classification brings about. I then briefly examine further distinguishing features of human interactive kinds.